Local Language Maintenance Based on the Story of the Mekongga People in Kolaka District Southeast Sulawesi Province - Rahmat Sewa Suraya; Akhmad Marhadi; Alias; Wilma Akihary; Patresia Silvana Apituley; Rita Fransina Maruanaya (Britain International for Academic Research (BIAR-Publisher), 2021)
The socio-cultural condition of the Mekongga community in Kolaka Regency is known to have a lot of oral literature, one of which is folklore. The phenomenon of local language intimidation makes the Mekongga community in Kolaka Regency use the Mekongga folklore as the basis for maintaining their regional languages. Scientific studies on the phenomenon of folklore-based local language defense are still rarely carried out, especially the Mekongga folklore. Therefore, the purpose of this study is to analyze and describe the maintenance of regional language based on the Mekongga folklore in Kolaka Regency. This study uses a qualitative approach with informant determination techniques using purposive sampling technique. Methods of data collection in this study using the method of observation, interviews, and documentation. Meanwhile, the data collected was analyzed using a qualitative descriptive technique. The results of this study indicate that regional language maintenance based on the Mekongga folklore in Kolaka Regency is carried out in several aspects, namely: 1) Regional language preservation through the family environment by presenting the Mekongga folk tales as bedtime stories or telling them as spare time. 2) the preservation of regional languages through the association of children, namely folklore is used as an empty time filler when playing or used to tell each other when gathering before starting a game. 3) the preservation of regional languages through the educational environment, namely becoming a wealth of local wisdom as local content in schools. The publication of folklore in local content is intended to attract students' interest in learning local languages.